Another perspective on the age and origin of the Berelyokh mammoth site (northeast Siberia). Issue 2 (27th February 2018) - Lozhkin, Anatoly V.; Anderson, Patricia M.
Abstract: The Berelyokh site includes an exceptional bone horizon consisting of 8431 remains of Mammuthus primigenius. Previous investigations, spanning ~40 years, concluded that the deaths and bone concentration were caused by spring flooding, possibly related to wetter Bølling climates. We review work from these studies with emphasis on under-reported palynological data to provide more detail on paleoenvironmental reconstructions and an alternative interpretation for the age and origin of the bone bed. Palynological results suggest the horizon formed under cool conditions of the last glacial maximum, rather than during a Bølling-type oscillation. Presence of permafrost features and associated tundra pollen taxa in the Berelyokh sections suggest that thermokarst processes, unrelated to climate change, could account for the formation of the bone horizon. The penetration of surface waters into frozen sediments of a high floodplain terrace resulted in the formation of hidden thaw sinks. As thaw continued, the pits expanded with surface soils supported by a viscous water-sediment mixture. The weakened surface gave way under the weight of the mammoths, with the hillside collapsing either due to the animals' struggles or destabilization related to the thaw sinks. This scenario highlights the hazards of thermokarst terrain for present and future populations of northern animals.